Examining micro-cavity parameters of top emission organic light-emitting diode with low-order resonant modes - 曹进 王立 张建华 (Journal of Shanghai University, 2011)
Emission characteristics of top emitting organic light-emitting devices （TOLEDs） with Ag as reflective anode, Al/Ag as semitransparent cathode and 90 160 nm [N-（1-naphthyl）-N-phenyl-amino] biphenyl/tris-（8-hydroxy quinoline） aluminum （NPB/Alq3） sandwiched in the electrodes are examined. The electroluminescence （EL） spectra of the TOLEDs are simulated based on the Fabry-Perot cavity theory. And the resonant modes in cavity structure of TOLEDs is discussed and clarified which can accurately describe the work principle of the devices. A fairly good match between calculated values and experimental data is achieved at different emission colors from bluish green to orange.